(The effect of personal and family factors in the establishment of pilot project (Field study on Higher Education students in Dhofar Governorate - Koufan, Ahmed Hamed Ahmed; Hamami, Samir Marwan (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed to investigate the impact of personal factors and family and the surrounding environment in the establishment of the pilot project and to identify the relative importance of each factor of personal factors, and analysis of statistical relationship between them and the establishment of the private project, who plays the role of great importance in the development of economic development and community-based organizations, the multiplicity of sources of income, providing job opportunities for the high rate, where formed a sample search of (474) personnel, university professors and university students, as was the distribution of (474) identification. It was tested hypotheses search containing statistical method descriptive, and testing and analysis Al-ameli Factor analysis and the use of the regression technique between the variables using the statistical program SPSS.
Keywords: personal factors; family factors; pioneering project; private project